2014
DOI: 10.1007/s00384-013-1820-8
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, risks and outcome of radiological leak following early contrast enema after anterior resection

Abstract: In the current series, early Gastrografin enema following anterior resection identifies a 14 % radiological leak rate and has a high sensitivity and specificity for predicting clinical AL. The majority of radiological leaks may be managed conservatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 24 publications
0
15
0
1
Order By: Relevance
“…Although hypothetical, one could argue that the observed difference in anastomotic leakage was related to differences in immune response and thus to wound and anastomotic healing. However, other studies regularly reported higher rates of anastomotic leakage in male patients in comparison to females [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Although hypothetical, one could argue that the observed difference in anastomotic leakage was related to differences in immune response and thus to wound and anastomotic healing. However, other studies regularly reported higher rates of anastomotic leakage in male patients in comparison to females [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 98%
“…Data on clinical and oncologic outcome after surgery for rectal cancer with regard to gender are limited. On the one hand, some studies suggest that anastomotic leakage occurs more frequently in male than in female patients after anterior resection [ 13 , 14 ]. Also, male sex may imply a higher risk for in-hospital mortality [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study from 2014, which included 129 patients with low anterior resection, the ISREC definition and severity-grading system was applied. Of 19 patients with contrast enema proven AL, 61% had grade A, 17% grade B, and 22% grade C [ 15 ]. These results show that this new grading system has its own shortcomings.…”
Section: Discussionmentioning
confidence: 99%
“…A full blood count, CRP measurement and a renal profile were performed daily until the day of discharge. Sixty‐seven per cent of patients underwent a routine gastrograffin enema between postoperative days 3 and 5 based on consultant preference, as previously described . Patients suspected of having AL before the gastrograffin enema, or a leak not detected by the gastrograffin enema, underwent CT of their abdomen and pelvis.…”
Section: Methodsmentioning
confidence: 99%